Shocks and coping: Findings from the sixth round of the Myanmar Household Welfare Survey (June – November 2023) - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
The sixth round of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey, was implemented between August and November 2023. It follows five rounds that were carried out since the beginning of December 2021. This report discusses the findings from the sixth round related to shocks and coping strategies. The security situation in Myanmar continued to deteriorate during the sixth-round recall period, which spanned from June to November 2023. Households felt insecure in their communities, as reported by 23 percent of households and had a low level of trust, as reported by 25 percent of households. This is because crime and violence continued to increase, affecting 20 and 10 percent of communities, respectively. Further, eight percent of households were directly affected by violence, either through violence against a household member, robbery, or appropriation and/or destruction of their assets. Lawlessness continues to rise in Myanmar. In June–November 2023, 21 percent of households reported a lot or some gambling in their community, 20 percent reported a high risk of burglary, theft, or robbery in their community, and 16 percent reported drug use. These issues were more prominent in urban areas, compared to rural areas. Another crucial challenge is that 15 percent of respondents felt that it was dangerous for them to move around and do everyday tasks in June–November 2023. Finally, three percent of respondents revealed that there was a risk of kidnapping in their community. The two states/regions where households felt the most insecure between June and November 2023 were Kayah and Chin. At the same time, the security situation in Rakhine, Tanintharyi, and Sagaing decreased the most compared to the same time last year. These areas witnessed the highest increases in lawlessness. While the lowest levels of reported insecurity continued to be in Ayeyarwady, Bago, and Nay Pyi Taw, these regions are still confronting much of the same risks as experienced across the country. Households faced multiple shocks besides insecurity. In June–November 2023, 19 percent of farm households reported being negatively impacted by at least one climatic shock. Intense wind was a major issue in Rakhine with 28 percent of households negatively impacted. Disruptions to the internet and electricity also negatively affected household wellbeing and livelihoods. For residents that accessed electricity from the national power grid, 55 percent of households had a power cut of at least one hour from 8:00 am to 8:00 pm all seven days of the week prior to the interview. Further, between June and November of 2023, almost half of the households (48 percent) did not have access to the internet regularly. Access to medical services and school enrolment improved at the end of 2023 compared to the end of 2022. The percentage of households who could never access medical services dropped from eight percent in July–December 2022 to two percent in June–November 2023. School enrollment improved from 79 percent of children aged 5 to 14 enrolled in July-December 2022 to 86 percent of children enrolled in June–November 2023. The rate of food inflation rose to 24 percent between March–June 2023 and September-November 2023, on average 5 percent per month. The prices of most foods in our survey increased considerably in the one-year period between October–December 2022 and September–November 2023, with median rice prices increasing by 75 percent. Further, the contribution of rice prices to the rising cost of the food inflation basket has become more 4 important over time. On the other hand, vegetable prices exhibited substantial volatility with large increases in prices between the third and fourth quarters of both 2022 and 2023. Seventy-five percent of households used at least one coping strategy to meet daily needs during the month prior to the sixth-round survey (June–November 2023). The three most common coping strategies used were spending savings, reducing non-food expenditure, and reducing food expenditure. This has been consistent across rounds. Further, some households exhausted some or all of their coping strategies. Thirty-five percent of households reported that they no longer have any savings to reduce. Finally, the number of households who borrowed money (30 percent) decreased significantly from the previous year (38 percent) but was still slightly higher than in the beginning of 2023. At the same time, 49 percent of households continued to be in debt.